Latest improvements of microchannel-plate PMTS - Lehmann, Albert; Böhm, Merlin; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The DIRC detectors of the P̄ANDA experiment at FAIR will use multi-anode MCP-PMTs as photon sensors. After long and extensive R&D work the performance parameters of the recent 2” MCP-PMT models are converging towards the required values. The lifetime of most ALD-coated MCP-PMTs is well surpassing the DIRC requirements with the best tube currently reaching >22 C/cm2 integrated anode charge without aging. The performance of the most advanced MCP-PMTs from PHOTONIS and Hamamatsu fulfill basically all requirements with a highlight being the high detective quantum efficiency (DQE) of almost 30% for the PHOTONIS 9002108. The improvements of the latest MCP-PMT models compared to former tubes are emphasized in this paper. In addition, some performance features of a recently developed 2” MCP-PMT by Photek Ltd are presented and discussed.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Atomic layer deposition (ALD); Cherenkov detectors; Lifetime; Microchannel-plate photomultipliers

Latest Technological Advances with MCP-PMTs - Lehmann, Albert; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; Böhm, Merlin; et al. (Journal of Physics: Conference Series, 2022)
This paper discusses the most recent advances with 2-inch MCP-PMTs. The status in terms of lifetime, detection efficiency, rate capability, time resolution, and gain behavior in magnetic fields are summarized. Significant progress in collection (CE) and quantum efficiency (QE) led to an excellent detection efficiency DQE = QE∗CE of â1/430%. With a new DAQ setup up to several hundred anode pixels can be read out simultaneously in 3D allowing a glance "inside the PMT". Parameters like dark count rates and ion afterpulsing are measurable as a function of the incident photon position as well as the temporal and spacial spread of recoil electrons and electronic and charge-sharing crosstalk even inside a magnetic field.
CRIS-Team Scopus Importer:2022-12-30

Particle identification algorithms for the PANDA barrel DIRC - Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at the international accelerator Facility for Antiproton and Ion Research in Europe (FAIR) near GSI, Darmstadt, Germany will address fundamental questions of hadron physics. Excellent particle identification is required to achieve the PANDA physics goals. Hadronic particle identification (PID) in the barrel region of PANDA target spectrometer will be delivered by a fast focusing DIRC (Detection of Internally Reflecfted Cherenkov light) counter. The Barrel DIRC will cover the polar angle range of 22◦-140◦ and is designed to provide π/K separation for momenta up to 3.5 GeV/c with a separation power of at least 3 standard deviations. Several reconstruction algorithms have been developed to determine the performance of the detector. The “geometrical reconstruction” determines the Cherenkov angle by relying primarily on the position of the detected photons. The “time imaging”, however, utilizes both position and time measurements by directly performing the maximum likelihood fit. Simulations and experimental data from prototype tests at the CERN Proton Synchrotron (PS) were used to evaluate the performance of the algorithms. We will discuss both reconstruction approaches.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Detector modelling and simulations I; Interaction of hadrons with matter etc; Interaction of photons with matter; Interaction of radiation with matter; Particle identification methods; Performance of High Energy Physics Detectors

Particle identification with DIRCs at PANDA - Düren, M.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The DIRC technology (Detection of Internally Reflected Cherenkov light) offers an excellent possibility to minimize the form factor of Cherenkov detectors in hermetic high energy detectors. The PANDA experiment at FAIR in Germany will combine a barrel-shaped DIRC with a disc-shaped DIRC to cover an angular range of 5 to 140 degrees. Particle identification for pions and kaons with a separation power of 3 standard deviations or more will be provided for momenta between 0.5 GeV/c and 3.5 GeV in the barrel region and up to 4 GeV/c in the forward region. Even though the concept is simple, the design and construction of a DIRC is challenging. High precision optics and mechanics are required to maintain the angular information of the Cherenkov photons during multiple internal reflections and to focus the individual photons onto position sensitive photon detectors. These sensors must combine high efficiencies for single photons with low dark count rates and good timing resolution at high rates. The choice of radiation hard fused silica for the optical material and of MCP-PMT photon sensors is essential for DIRC detectors to survive in an environment of radiation and strong magnetic field. The two DIRC detectors differ in the focusing optics, in the treatment of chromatic dispersion and in the electronic readout systems. The technical design of the two DIRC detectors and their validation by testing prototypes in a mixed particle beam at CERN are presented.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Cherenkov-detector; PANDA; Particle identification

Performance of the most recent MCP-PMTs - Böhm, Merlin; Krauss, S.; Lehmann, Albert; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; et al. (Journal of Instrumentation, 2020)
For the identification of charged and fast moving particles two DIRC (detection of internally reflected Cherenkov light) detectors are being built for the PANDA experiment. They will provide hadronic particle identification in the PANDA target spectrometer and require lifetime-enhanced MCP-PMTs as sensors. MCP-PMTs are the only viable option for this task because they work in high magnetic fields of > 1 Tesla, have low dark count rates and an excellent time resolution of < 120 ps RMS. The tubes being deployed in the experiment have to be tested to find out if they comply with these requirements. These tests are performed in a semi-automatic setup which allows to measure time resolution, dark count rate, afterpulse probability, crosstalk behaviour, quantum efficiency, and gain distribution. The measurements are done with a picosecond laser attached to a 3-axis stepper to scan the sensor surface. Measurements and results of close-to-final prototype tubes are presented here.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Cherenkov detectors; Photon detectors for UV; Photon detectors for UV; Visible and IR photons (vacuum); Visible and IR photons (vacuum) (photomultipliers HPDs others)

Precision resonance energy scans with the PANDA experiment at FAIR: Sensitivity study for width and line shape measurements of the X(3872) - Barucca, G.; Davi, F.; Lancioni, G.; Mengucci, P.; Montalto, L.; Natali, P. P.; Paone, N.; Rinaldi, D.; Scalise, L.; Erni, W.; Krusche, B.; Steinacher, M.; et al. (European Physical Journal A, 2019)
.This paper summarises a comprehensive Monte Carlo simulation study for precision resonance energy scan measurements. Apart from the proof of principle for natural width and line shape measurements of very narrow resonances with PANDA, the achievable sensitivities are quantified for the concrete example of the charmonium-like X(3872) state discussed to be exotic, and for a larger parameter space of various assumed signal cross-sections, input widths and luminosity combinations. PANDA is the only experiment that will be able to perform precision resonance energy scans of such narrow states with quantum numbers of spin and parities that differ from JPC=1–.
CRIS-Team WoS Importer:2019-04-12

Recent progress with microchannel-plate PMTs - Lehmann, Albert; Böhm, Merlin; Miehling, Daniel; Pfaffinger, Markus; Stelter, Samuel; Uhlig, Fred; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
Microchannel-plate (MCP) PMTs were identified as the only suitable photon sensors for the two DIRC detectors of the P̄ANDA experiment at FAIR. As the long-standing aging problem of MCP-PMTs was recently overcome by coating the MCP pores with an atomic layer deposition (ALD) technique, further improved 2″ MCP-PMTs were investigated. The best PHOTONIS device has reached a lifetime of >20 C/cm2 integrated anode charge without any sign of aging. Also the newly developed 2″ MCP-PMTs of Hamamatsu are maturing and are usable in high rate environments. The status of our long-term lifetime measurements and the performance parameters of the currently most advanced ALD-coated MCP-PMTs from PHOTONIS and Hamamatsu are presented. In addition, first results obtained with a new quality assurance setup for MCP-PMTs are discussed. This setup consists of a high performance DAQ system to measure the response of ≥64 anode pixels simultaneously. The system allows to study and quantify background parameters like position dependent dark count rates and ion afterpulsing as well as temporal and spacial distributions of recoil electrons and the effects of electronic and charge-sharing crosstalk among the anode pixels.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Atomic layer deposition (ALD); Cherenkov detectors; Lifetime; Microchannel-plate photomultipliers

Status of the PANDA Barrel DIRC - Schwarz, C.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment will use cooled antiproton beams with high intensity stored in the High Energy Storage Ring at FAIR. Reactions on a fixed target producing charmed hadrons will shed light on the strong QCD. Three ring imaging Cherenkov counters are used for charged particle identification. The status of the Barrel DIRC (Detection of Internally Reflected Cherenkov light) is described. Its design is robust and its performance validated in experiments with test beams. The PANDA Barrel DIRC has entered the construction phase and will be installed in 2023/2024.
CRIS-Team WoS Importer:2020-05-08

Status of the PANDA Endcap Disc DIRC project - Koeseoglu; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at FAIR near Darmstadt, Germany, is under construction, planned to investigate fundamental questions of hadron physics with a fixed proton target by using an antiproton beam within a momentum range of 1.5 to 15 GeV/c. A novel Cherenkov detector, the Endcap Disc DIRC (EDD), has been developed to separate pi(+/-) and K-+/- by at least 3 standard deviation up to 4 GeV/c. It will cover the polar angle range of the forward endcap of the PANDA target spectrometer from 5 degrees to 22 degrees. The EDD uses a 2 cm thick fused silica radiator plate with focusing elements at the outer rim and lifetime-enhanced Microchannel-PlatePMTs (MCP-PMTs) as light sensors. The Cherenkov radiator of the EDD consists of four identical independent quadrants, polished with highest precision in order to conserve the internally reflected Cherenkov angle during light propagation. This manuscript confirms basic functionalities of the EDD design and tests of the prototype with particle beams at CERN in 2018.
CRIS-Team WoS Importer:2020-05-08

Systematic approach to measure the performance of microchannel-plate photomultipliers - Lehmann, Albert; Böhm, Merlin; Götz, Klaus; Gumbert, Katja; Krauss, Steffen; Miehling, Daniel; Pfaffinger, Markus (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2024)
In this paper, we present our approach to systematically measure numerous performance parameters of microchannel plate photomultiplier tubes. The experimental setups, the analyses and selected results are discussed. Although the techniques used may be different in other locations, the document is intended as a guide for comparable measurements with other types of microchannel plate photomultiplier tubes. Measurements are shown for the following performance parameters: spectral and spatial quantum efficiency, collection efficiency, gain as a function of voltage, position and magnetic field, time resolution, rate capability and lifetime. By using a dedicated 3-axis stepper and an FPGA-based data acquisition system, also inner PMT parameters are measured as a function of the active area, such as relative detection efficiency, dark count rate, time resolution, recoil electron and afterpulse distributions, as well as charge sharing and electronic crosstalk. In addition, some of the parameters are investigated inside a strong magnetic field. For many of these measurements, the change of most setup parameters and the subsequent analysis can be controlled semi-automatically by software scripts.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Afterpulses; Collection efficiency; Crosstalk; Dark count rate; Gain; Lifetime; Magnetic field; Multianode microchannel-plate PMTs; PANDA; Performance parameters; Quantum efficiency; Rate capability; Recoil electrons; Time resolution

Technical design report for the (P)over-barANDA Barrel DIRC detector - Singh, B.; Erni, W.; Krusche, B.; Steinacher, M.; Walford, N.; Liu, B.; Liu, H.; Liu, Z.; Shen, X.; Wang, C.; Zhao, J.; Albrecht, M.; et al. (Journal of Physics G: Nuclear and Particle Physics, 2019)
The (P) over bar ANDA (anti-Proton ANnihiliation at DArmstadt) experiment will be one of the four flagship experiments at the new international accelerator complex FAIR (Facility for Antiproton and Ion Research) in Darmstadt, Germany. (P) over bar ANDA will address fundamental questions of hadron physics and quantum chromodynamics using high-intensity cooled antiproton beams with momenta between 1.5 and 15 GeV/c and a design luminosity of up to 2 x 10(32) cm(-2) S-1. Excellent particle identification (PID) is crucial to the success of the (P) over bar ANDA physics program. Hadronic PID in the barrel region of the target spectrometer will be performed by a fast and compact Cherenkov counter using the detection of internally reflected Cherenkov light (DIRC) technology. It is designed to cover the polar angle range from 22 degrees to 140 degrees and will provide at least 3 standard deviations (s.d.) pi/K separation up to 3.5 GeV/c, matching the expected upper limit of the final state kaon momentum distribution from simulation. This documents describes the technical design and the expected performance of the (P) over bar ANDA Barrel DIRC detector. The design is based on the successful BaBar DIRC with several key improvements. The performance and system cost were optimized in detailed detector simulations and validated with full system prototypes using particle beams at GSI and CERN. The final design meets or exceeds the PID goal of clean pi/K separation with at least 3 s.d. over the entire phase space of charged kaons in the Barrel DIRC.
CRIS-Team WoS Importer:2019-03-15

The Endcap Disc DIRC detector of PANDA - Föhl, K.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Götzen, K.; Krebs, M.; Lehmann, D.; Nerling, F.; Patsyuk, M.; Peters, K.; Schepers, G.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
At the international FAIR laboratory, an upcoming significant enlargement of the GSI installations near Darmstadt, Germany, the PANDA antiproton experiment will investigate fundamental questions of hadron physics in the charm quark energy range. Antiprotons in the 1.5 to15 GeV/c momentum range will interact with gas jet or pellet fixed targets. The Endcap Disc DIRC (Detection of Internally Reflected Cherenkov light) covers the forward endcap solid angle of the PANDA target spectrometer to positively identify charged kaons. Monte-Carlo simulations indicate that from 1 up to 4 GeV/c one can achieve kaon–pion separation with a separation power of at least 3 standard deviations. For the upcoming CERN test beam in August 2018 the read-out electronics has been upgraded to the TOFPET-ASIC Version 2.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Cherenkov light; DIRC; Particle identification

The endcap disc DIRC for PANDA at FAIR - Schmidt, M.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; et al. (Nuovo Cimento Della Societa Italiana Di Fisica C, 2019)
The Endcap Disc DIRC for the PANDA experiment is going to provide an excellent particle identification up to particle momenta of 4GeV/c. It covers the polar angles from 5° to 22° and guarantees a separation power of more than 3 standard deviations (s.d.) for pions and kaons in the required phase space. The simulated detector performance has been validated during several testbeam campaigns. Additionally, the transmission losses of the optical filter has been investigated to estimate the filter performance at the end of the PANDA lifetime.
CRIS-Team Scopus Importer:2019-07-19

The innovative design of the endcap disc DIRC detector for PANDA at FAIR - Schmidt, M.; Duren, M.; Etzelmüller, E.; Föhl, K.; Hayrapetyan, A.; Köseoglu, I.; Kreutzfeld, K.; Rieke, J.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; et al. (Proceedings of the 2019 Meeting of the Division of Particles and Fields of the American Physical Society, DPF 2019, 2019)
The key component of the future PANDA experiment at FAIR is a fixed-target detector for collisions of antiprotons with a proton target up to a beam momentum of 15 GeV/c and is designed to address a large number of open questions in the hadron physics sector. In order to guarantee an excellent PID for charged hadrons in the polar angle range between 5° and 22°, a new type of Cherenkov detector called Endcap Disc DIRC (EDD) has been developed for the forward endcap of the PANDA target spectrometer. The desired separation power of at least 3 s.d. for the separation of π± and K± up to particle momenta of 4 GeV/c was determined with simulation studies and validated during various testbeam campaigns at CERN and DESY.
CRIS-Team Scopus Importer:2021-04-20

The innovative design of the PANDA Barrel DIRC - Schepers, G.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Nuovo Cimento Della Societa Italiana Di Fisica C, 2019)
The Barrel DIRC of the PANDA experiment at FAIR will cleanly separate pions from kaons for the physics program of PANDA. Innovative solutions for key components of the detector sitting in the strong magnetic field of the compact PANDA target spectrometer as well as two reconstruction methods were developed in an extensive prototype program. The technical design and present results from the test beam campaigns at the CERN PS in 2017 and 2018 are discussed.
CRIS-Team Scopus Importer:2019-07-19

The PANDA DIRC detectors - Etzelmüller, E.; Schwiening, J.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Traxler, M.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The PANDA experiment at the future Facility for Antiproton and Ion Research (FAIR) will address fundamental questions of hadron physics with unprecedented precision. To reach this goal excellent Particle Identification (PID) is essential over a large range of particle momenta and solid angles. Most of the phase space will be covered by two innovative DIRC (Detection of Internally Reflected Cherenkov light) detectors. The Endcap Disc DIRC and Barrel DIRC will cover the polar angle range from 5 to 22°and 22 to 140° respectively. Both detectors rely on high precision optical components, lifetime-enhanced Microchannel Plate PMTs (MCP-PMTs), and fast readout electronics.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Cherenkov detector; DIRC; MCP-PMT; Particle identification

The PANDA DIRCs - Schwarz, C.; Ali, A.; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The PANDA experiment at the FAIR facility adresses open questions in hadron physics with antiproton beams in the momentum range of 1.5-15 GeV/c. The antiprotons are stored and cooled in a High Energy Storage RING (HESR) with a momentum spread down to ∆p/p = 4 · 10−5. A high luminosity of up to 2 · 1032 cm−2s−1 can be achieved. An excellent hadronic particle identification (PID) will be provided by two Cherenkov detectors using the priciple of Detection of Internally Reflected Cherenkov light (DIRC). In the forward direction from polar angles of 5◦ to 22◦, the Endcap Disc DIRC (EDD) separates pions from kaons up to momenta of 4 GeV/c. Between 22◦ and 140◦ the Barrel DIRC cleanly separates pions from kaons for momenta up to 3.5 GeV/c. This article describes the design of the Barrel DIRC and of the Endcap Disc DIRC and the validation of their designs in particle beams at the CERN PS.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Data acquisition concepts; Detector design and construction technologies and materials; Performance of High Energy Physics Detectors

Time imaging reconstruction for the PANDA barrel DIRC - Dzhygadlo, R.; Ali, A.; Belias, A.; Gerhardt, A.; Krebs, M.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; et al. (Journal of Instrumentation, 2020)
The innovative Barrel DIRC (Detection of Internally Reflected Cherenkov light) counter will provide hadronic particle identification (PID) in the central region of the PANDA experiment at the new Facility for Antiproton and Ion Research (FAIR), Darmstadt, Germany. This detector is designed to separate charged pions and kaons with at least 3 standard deviations for momenta up to 3.5 GeV/c, covering the polar angle range of 22◦-140◦. An array of microchannel plate photomultiplier tubes is used to detect the location and arrival time of the Cherenkov photons with a position resolution of 2 mm and time precision of about 100 ps. The time imaging reconstruction has been developed to make optimum use of the observables and to determine the performance of the detector. This reconstruction algorithm performs particle identification by directly calculating the maximum likelihoods using probability density functions based on detected photon propagation time in each pixel, determined directly from the data, or analytically, or from detailed simulations.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Cherenkov detectors; Particle identification methods